Physical and structural properties of dysprosium doped barium borate glass / Mohamed Najmi Naquib Mohamed Zainal Abidin - Mohamed Zainal Abidin, Mohamed Najmi Naquib (Faculty Of Applied Sciences, 2017)
Six different glass samples have been prepared in this project by melt-quenching technique with composition (81-x)H3B03-19BaC03-xDy2O3, where x = 0.0, 0.2, 0.4, 0.6, 0.8, and 1.0 mol%. By varying the proportion of H3B03 and DY2O3, the effect of Dy2O3 to the barium borate glass can be investigated in terms of physical properties such as density and molar volume. The structural properties were measured by X-Ray Diffraction (XRD) technique and Fourier Tranform Infrared (FTIR) spectroscopy. Based on the result" it shows that the density and molar volume increases as the percent of DYz03 increases. The amorphous nature of this glass was proved from the XRD spectra. On the other hand, FTIR spectra showed the presence of Ba2+, B03, B04, B-O-B linkage, H-O-H and isolated borate on the glass network.